Pulmonary Recovery Following Corrective Surgery in Adult Patients With Severe Scoliosis: A Minimum of Five-Year Follow-Up - Zhou, Xin; Zhang, Zheng; Yang, Yue; Ma, Jun; Meng, Yichen; Wang, Ce; Zhou, Xuhui (Frontiers in Medicine, 2022)
Background: Halo gravity traction (HGT) has been reported to be a safe and effective adjunctive method for the management of scoliosis. However, the direct effects of HGT on the lung recovery of adult patients with scoliosis remain obscure. Objective: To investigate changes in lung volume and pulmonary function in adult patients with severe scoliosis who underwent posterior spinal fusion concomitant with preoperative halo gravity traction. Methods: A total of 47 patients with a minimum 5-year follow-up who underwent posterior spinal instrumentation and fusion using preoperative halo–gravity traction were analyzed. Pulmonary function tests and three-dimensional CT were performed to evaluate changes in lung function and lung volume, respectively. Results: There was no significant change in the Cobb angle of the major curve after halo gravity traction (P<0.0001=0.31). Significant improvement in both Cobb angle (P < 0.0001) and thoracic kyphosis (P < 0.001=0.034) after corrective surgery was observed. Pulmonary function did not change significantly during traction. However, a significant decline in absolute and percent-predicted pulmonary function values was noted following surgery. The average change in lung volume did not show statistical differences during traction. At 5-year postoperative follow-up, the mean values revealed a significant increase in total lung volume (P< 0.0001) and concave lung volume (P< 0.0001) with surgical correction, but no statistically significant change in lung volume on the convex side (P = 0.6957). Postoperative pulmonary complications occurred in 9 cases with lower preoperative pulmonary function, indicating the importance of performing PFT spirometry before corrective surgery. Conclusions: We found that halo gravity traction prior to corrective surgery was less useful in improving pulmonary function in adult patients with severe scoliosis. However, these patients were expected to have increased lung volume and improved lung function after correction of the deformity.